The use of size and growing height to improve Crassostrea gigas farming and breeding techniques against OsHV-1 - Azema, Patrick; Maurouard, Elise; Lamy, Jean-baptiste; Degremont, Lionel (Aquaculture, 2017)
Mortality associated with ostreid herpesvirus 1 (OsHV-1) has significantly impacted Crassostrea gigas farmers all around the world. Although selective breeding programs to improve OsHV-1 resistance can significantly reduce the mortality rate below 20%, husbandry practices have also been one way to limit or decrease mortality. The main objectives of this study were to describe the influence of two husbandry practices on OsHV-1-induced mortality in C. gigas spat and how different family lines respond to husbandry practices to gain a better understanding of the potential benefits of breeding management as a tool to adapt to improved practices. The first analysis investigated the importance of the size of C. gigas when challenged with OsHV-1 for the first time. For each of the 40 families of C. gigas evaluated, small (S) and large (L) oyster groups were tested for two years in the field. A significant mortality outbreak associated with OsHV-1 occurred during the first spring. At the end of the trial, the mean cumulative mortality of the L group (54.1%) was significantly lower than the mean cumulative mortality of the S group (74.8%), indicating the importance of size in OsHV-1-associated mortality. However, the overall effect of size was not consistent for all families: in 11 of the 40 families tested, there appeared to be no difference in mortality between the S and L groups. Observations at the family level allowed the identification of a large range of susceptibility to OsHV-1 regardless of the size group, with highly resistant families (<32%) and highly susceptible families (>80%). The second investigation compared different growing heights. Each of the 40 families was grown at three heights (high Hi, medium Me, and low Lo) corresponding to mean emersion times of 25, 12 and 2%, respectively. After an OsHV-1-related mortality outbreak, the mean mortality among the families was 91.6%, 88.0% and 86.9% for the Lo, Me and Hi conditions, respectively. Growing height had no effect in 31 of the 40 families tested, ...